Comparative Efficacy of Bio-Pesticide and Synthetic Agrochemicals on Population Control of Aphids, Helicoverpa armigera, Infestation Control and Yield of Okra: Population Control of Aphids, Helicoverpa armigera (Biological Sciences - PJSIR, 2020)
A field study was conducted at village Sardheri, district Charsadda for the year 2017 in order to evaluate the efficacy of bio-insecticides and synthetic agrochemicals against the aphids and Helicoverpa. armigera on Okra. There were eight treatments including control. The highest % reduction control of aphids after 3rd spray was 91.2 recorded for T6 treatment and T5 was the next superior treatment having a % reduction of 86.2. The highest percent reduction in pod damage (75.5%) was recorded for T6 after 3rd spray, while T5 was the next superior treatment and the pod borer damage was noted to be 72.2%. T5 yielded the highest mean produce of Okra per plant and was recorded to be 446.3 g. These findings revealed that bio-insecticide can be effectively used to control aphid population as well as the fruit infestation of Okra and improving the yield of Okra. The bio-insecticides can also lower the inputs of residues in the crops and pose least toxicity to non-targeted organism and also readily degradable.